Leisure Economy: Digitalisasi Event Desa Wisata Mangrove Mayangan - Haris Hermawan; Ahmad Nur Mahfuda (Indonesian Journal Publisher, 2023)
The development of tourist destinations in the village, as well as the promotion and marketing of culture, arts, and tourism are one of the flagship programs in Jember Regency, however, intense competition in the tourism world due to the impact of the COVID-19 pandemic, has forced villages to change the way they plan their tourism business. In order to survive, villages need to change from a resource-based business to a knowledge-based business/company (business based on knowledge), with the main characteristics of Technology, Information, Communication (ICT). When the main achievement of the village is sustainable competitive advantage or the achievement of sustainable business competitiveness, assistance is needed, assistance is aimed at encouraging village management in the process of achieving and developing knowledge as a village competitive strategy, then human resources need to be directed and fostered to utilize digital technology as a marketing medium at the same time. conduct direct interaction for tourism managers to interact with their customers.